EXTENT OF LOSSES INFLICTED BY APHID COMPLEX AT DIFFERENT LEVELS OF INFESTATION ON WHEAT AND DETERMINATION OF EIL AND ETL - RATHORE, LEEZA; SHARMA, PAWAN K (The Bioscan, 2016)
Field experiments were conducted at Experimental Farm of Department of Entomology, CSK HPKV, Palampur, Himachal Pradesh during 2013-14 and 2014-15 to assess the losses caused by aphid complex in wheat. The aphid population at initial infestation levels of 5, 10, 20 and 40 aphids per plant released at CRI stage and peaked during 3rd week of March with the corresponding population of 26.7, 38.5, 38.9 and 38.5 aphids per plant and 25.2, 37.6, 38.1 and 39.0 aphids per plant during 2013-14 and 2014-15, respectively. The highest avoidable losses in grain yield were 28.64 and 26.67 per cent during 2013-14 and 2014-15, respectively. Tillering stage showed higher yield losses and thus proved to be the most susceptible stage. EIL determined for aphids for the infestation initiated at CRI was 32.61 CAD (Cumulative aphid days) and at tillering and panicle emergence stages the corresponding EIL values were 41.55 and 35.77 CAD per plant and the ETL values were 24.46, 31.16 and 26.83 CAD per plant, respectively. On the basis of initial aphid infestation levels, the EIL was 14.93, 7.19 and 6.78 aphids per plant and the ETL values were 11.20, 5.39 and 5.09 aphids per plant at CRI, tillering and panicle emergence.